2019
DOI: 10.1111/exd.14049
|View full text |Cite
|
Sign up to set email alerts
|

SERPINB2 and miR‐146a/b are coordinately regulated and act in the suppression of psoriasis‐associated inflammatory responses in keratinocytes

Abstract: Psoriasis is a chronic inflammatory skin disease with numerous involved factors. miR‐146a and miR‐146b (miR‐146a/b) are anti‐inflammatory miRNAs that are increased in psoriatic skin. SERPINB2 has been shown to be upregulated in the inflammation and infections. Here we aimed to study the relationship between miR‐146a/b and SERPINB2 and to delineate the role of SERPINB2 in association of plaque psoriasis. We report increased SERPINB2 expression in the skin of psoriasis patients, which was in a positive relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 63 publications
2
21
0
Order By: Relevance
“…SERPINB2 is highly expressed during inflammation, infection, and tissue damage, indicating its immune features [24,25]. A previous study revealed that SERPINB2 and miR-146a-5p are highly expressed in psoriatic skin and SERPINB2 was suppressed by miR-146a-5p [26]. Our study revealed that SERPINB2 inhibition could reduce the differentiation of Th2 cells, whereas its overexpression exhibited reversed effects.…”
Section: Discussionsupporting
confidence: 49%
“…SERPINB2 is highly expressed during inflammation, infection, and tissue damage, indicating its immune features [24,25]. A previous study revealed that SERPINB2 and miR-146a-5p are highly expressed in psoriatic skin and SERPINB2 was suppressed by miR-146a-5p [26]. Our study revealed that SERPINB2 inhibition could reduce the differentiation of Th2 cells, whereas its overexpression exhibited reversed effects.…”
Section: Discussionsupporting
confidence: 49%
“…The miR‐146 family consists of miR‐146a and miR‐146b (miR‐146a/b) that differ by only two nucleotides in their 3′ region, which is considered less significant for their interaction with mRNA targets. As such, miR‐146a/b has been reported to have a similar set of target genes 22–24 . Previous studies have demonstrated that multiple components, including interleukin‐1 receptor‐associated kinase 1 (IRAK1) and caspase recruitment domain 10 (CARD10), from the NF‐κB pathway are directly targeted by miR‐146a/b 23,25 .…”
Section: Introductionmentioning
confidence: 99%
“…As such, miR-146a/b has been reported to have a similar set of target genes. [22][23][24] Previous studies have demonstrated that multiple components, including interleukin-1 receptor-associated kinase 1 (IRAK1) and caspase recruitment domain 10 (CARD10), from the NF-κB pathway are directly targeted by miR-146a/b. 23,25 Accordingly, overexpression of miR-146a/b has been shown to suppress endogenous levels of IRAK1 and CARD10 and of NF-κB-inducible chemokines IL-8 and chemokine (C-X-C motif) ligand 1 (CXCL1) in multiple cell types, including human bronchial epithelial cells (HBECs).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, miR-125a can repress inflammation in intestinal mucosa obtained from patients with inflammatory bowel disease (IBD) through modulating E26 transformation-specific-1 (ETS-1) [11]. Previously, accumulating studies elucidated that miRNAs are involved in various aspects of psoriasis, such as mediating inflammatory responses and regulating cell functions in keratinocytes [12, 13]. These findings all suggest that miR-125a is intimately related to the inflammation and immunity regulation.…”
Section: Introductionmentioning
confidence: 99%